Comparison of algorithm RSA with algorithm Blowfish in Data Security Application Design - Rahayu, Ade; Ardana, Amanda Putri; Pramudhita, Chika; Syafitri, Dea; Siregar, Rianty Zabitha (Journal of Mathematics and Technology (MATECH), 2024)
In the development of information technology that is increasingly high and increasing, as well as sophisticated times like this, tools are needed to send messages, including many media such as chat, line or the like so that we can send messages quickly and vice versa. Of all the conveniences that will certainly be very influential when we will send messages whose contents only certain people who have the right to know the contents. One that must be really vigilant and careful is a message that is confidential because if the message is spread it will have a bad impact on ourselves or others. Beberapacara can be used, one of them by securing information data by using cryptographic concepts related to information security aspects, the integrity of a data. The cryptography algorithm that will be used to solve the problem of securing information or data is by using RSA method and Blowfish algorithm method. Encryption results from the word UPI YPTK obtained results by using the RSA method that is obtained decimal results: 98 135 98 0 113 9 9 84 98 34 98 0 98 49 113 135, and the result of the encryption process using the Blowfish algorithm is Ü|*œ / 9".